Viral Justice: TikTok Activism, Misinformation, and the Fight for Social Change in Southeast Asia - Nuurrianti Jalli (Social Media + Society)
This study examines the use of TikTok as a platform for youth activism in Southeast Asia, focusing on Indonesia, Malaysia, and the Philippines. Through a mixed-methods approach that includes qualitative content analysis, semi-structured interviews, systematic fact-checking, and digital trace data, the research explores how activists leverage TikTok’s unique features to promote social justice and mobilize political participation amid democratic backslidings. The findings reveal that activists skillfully adapt to TikTok’s attention economy, using strategies like trend-jacking and meme creation to reach broad audiences. However, they also face significant challenges, including rampant harassment and the precarious nature of algorithmic visibility. The study highlights the complexities of digital activism, where the pursuit of virality can sometimes undermine the depth of political movements. While the research counters the prevalent narrative that digital activism is rife with misinformation, it underscores the importance of maintaining accuracy to protect credibility. The study concludes by calling for further research on integrating online activism with offline organizing and exploring how platform governance can be reformed to better support activists. The insights from this study contribute to a deeper understanding of TikTok’s role in contemporary social movements and the challenges faced by youth activists in the digital age.